MANAGEMENT OUTCOME OF CLOSED FEMORAL SHAFT FRACTURES BY OPEN SURGICAL IMPLANT GENERATION NETWORK (SIGN) INTERLOCKING NAILS - Razaq, Mohammad Naeem-Ur-; Qasim, Muhammad; Khan, Muhammad Ayaz; Sahibzada, Ahmad Sohail; Sultan, Shahid (Journal of Ayub Medical College Abbottabad, 2009)
Background: Many hospitals in our country lack surgical expertise and operating room facilities like image intensifier and fractures table to carry out closed interlocking nails (ILN) in femoral shaft fractures. But availability of Surgical Implant Generation Network (SIGN) interlocking nails & nailing instrumentation have made open ILN of these fractures possible at very basic level of our health care system. We have carried out open SIGN nailing in patients with closed fractures of shaft femur without the use of image intensifier. Result for fracture union was evaluated both clinically and radio-logically, and graded at 8 months (32 weeks) after treatment by Thoressen’s criteria. Methods: An experimental study of open SIGN nailing was carried out on 47 patients with fractures shaft of femur who had been admitted to our tertiary care hospital from January 2006 to December 2007. Inclusion criteria were adult patients older than 16 years with closed fractures of the shaft femur, and have presented within a week of the injury, and have not had any previous surgical treatment for the fracture. Malnourished patients and patients with open, pathological fractures and non union cases were excluded from the study. A standard protocol was followed on all patients, which is describing below. The data obtained was analysed using SPSS. Results: The union rate was 97.83% in open nailing at 32 weeks after surgery and the Mean±SD time to union was 19.65±5.19 weeks (ranges from 16-32 weeks).We obtained excellent results in 39 patients (83.33%), good in 4 patients (8.50%), fair in 3 patients (6.38%) and poor in one (2.12%). Conclusions: The open SIGN nailing, without the use of image intensifier, for treatment of closed fractures of shaft femur achieves excellent result in term of fracture union. Results obtained are comparable to the results of closed interlocking nailing, requires less expertise and resources, and its use is recommended for long bones fracture care at the very level of our health care system. Keywords: SIGN nailing, Interlocking nailing, Image intensifier, Closed femoral shaft fracture, image intensifier